Sex-Specific Comparative Effectiveness of Oral Anticoagulants in Elderly Patients With Newly Diagnosed Atrial Fibrillation. Issue 4 (April 2017) - Palamaner Subash Shantha, Ghanshyam; Bhave, Prashant D.; Girotra, Saket; Hodgson-Zingman, Denice; Mazur, Alexander; Giudici, Michael; Chrischilles, Elizabeth; Vaughan Sarrazin, Mary S.
Abstract : Background—: Sex-specific comparative effectiveness of direct oral anticoagulants among patients with nonvalvular atrial fibrillation is not known. Via this retrospective cohort study, we assessed the sex-specific, comparative effectiveness of direct oral anticoagulants (rivaroxaban and dabigatran), compared to each other and to warfarin among patients with atrial fibrillation. Methods and Results—: Elderly (aged ≥66 years) Medicare beneficiaries enrolled in Medicare Part D benefit plan from November 2011 to October 2013 with newly diagnosed atrial fibrillation formed the study cohort (65 734 [44.8%] men and 81 137 [55.2%] women). Primary outcomes of inpatient admissions for ischemic strokes and major bleeding were compared across the 3 drugs (rivaroxaban: 20 mg QD, dabigatran: 150 mg BID, or warfarin) using 3-way propensity-matched samples. In men, rivaroxaban use decreased stroke risk when compared with warfarin use (hazard ratio, 0.69; 95% confidence interval, 0.48–0.99; P =0.048) and dabigatran use (hazard ratio, 0.66; 95% confidence interval, 0.45–0.96; P =0.029) and was associated with a similar risk of any major bleeding when compared with warfarin and dabigatran. In women, although ischemic stroke risk was similar in the 3 anticoagulant groups, rivaroxaban use significantly increased the risk for any major bleeding when compared with warfarin (hazard ratio, 1.20; 95% confidence interval, 1.03–1.42; P =0.021) and dabigatran (hazard ratio, 1.27; 95% confidence interval, 1.09–1.48; P =0.011). Conclusions—: The reduced risk of ischemic stroke in patients taking rivaroxaban, compared with dabigatran and warfarin, seems to be limited to men, whereas the higher risk of bleeding seems to be limited to women. Abstract : Supplemental Digital Content is available in the text.